Ultrasound-based prediction of fetal hyperinsulinemia: development of a fetal metabolic score - Roberto Noya Galluzzo; Karine Souza Da Correggio; Aldo von Wangenheim; Heron Werner; Edward Araujo Júnior; Gustavo Yano Callado; Alexandre Sherlley Casimiro Onofre (Journal of Perinatal Medicine, 2026)
Abstract Objectives Gestational diabetes mellitus (GDM) is associated with fetal hyperinsulinemia, excessive adiposity, and adverse perinatal outcomes; sonographic markers of fetal adiposity, liver enlargement, and septal thickening may allow direct assessment of fetal metabolic adaptation. This study aimed to develop an ultrasound-based fetal metabolic score (FMS) estimating the risk of fetal hyperinsulinemia. Methods The FMS was developed from a prospective cohort of 223 pregnant women (128 with GDM, 95 controls). Sonographic markers of neonatal hyperinsulinemia were identified using umbilical cord C-peptide above the 75th percentile as the reference outcome: thigh soft tissue thickness, abdominal subcutaneous fat thickness, fetal liver length, and interventricular septal thickness. Odds ratios from logistic regression were converted into weighted integer coefficients, and continuous measurements were categorized by gestational age-adjusted percentiles into a composite score. Results Fetuses of GDM mothers showed significantly greater abdominal adiposity, liver length, and interventricular septal thickness than controls. Thigh soft tissue thickness (OR 1.62; 95 % CI 1.25–2.09; p